System-wide and banks' internal stress tests: Regulatory requirements and literature review - Kamil Pliszka (Deutsche Bundesbank, 2021)
This paper deals with both system-wide and banks' internal stress tests. For system-wide stress tests it describes the evolution over time, compares the stress test design in major jurisdictions, and discusses academic research. System-wide stress tests have gained in importance and nowadays serve as a key regulatory tool. For instance, they feed into the calculation of capital requirements in the EU. The literature shows that the disclosure of stress test results reveals new information to the market. Furthermore, banks that participate in system-wide stress tests increase their capital ratios and shift lending to less risky borrowers. For banks' internal stress tests, this paper gives an overview of the regulatory requirements under Pillars 1 to 3 of Basel III and reviews the academic literature. Stress testing is deeply embedded in the Basel III framework. Banks that choose to apply internal models for calculating capital requirements are subject to more stringent stress testing requirements and, for example, have to ensure capital adequacy if the internal risk parameters are being stressed. The academic research on banks' internal stress tests shows that stress scenarios derived from expert judgment should be complemented by scenarios which are selected on the basis of algorithms that consider historical characteristics of the risk factors. Furthermore, banks' conventional credit risk models can be modified and used for stress testing. As stress testing is exposed to considerable model and estimation risk, banks should carry out extensive robustness checks. In sum, both system-wide and banks' internal stress tests play a complementary role in ensuring the resilience of individual banks and the financial system to adverse shocks.
Keywords: G21; G32; G38; 330; literature survey; regulatory expectations; regulatory requirements; stress testing